Measuring Well-being and Progress in Countries at Different Stages of Development Towards a More Universal Conceptual Framework - Boarini, Romina (OECD Development Centre Working Papers, 2014)
A wide range of voices around the world have stressed the need to understand development as a multidimensional phenomenon that involves and affects many aspects of people's lives. Increasingly, it is recognised that current well-being and its long-term sustainability are the ultimate goals of development and that these notions better capture the human experience of development. The objectives of this paper are to explain why well-being matters in countries at different levels of development and to address measurement challenges in the context of developing countries. These objectives are pursued in four main steps. First, the paper offers a conception of well-being and illustrates its relevance in different development contexts. Second, it describes briefly how the measurement of well-being is implemented under the OECD Better Life Initiative for OECD countries. Third, it proposes ways in which the OECD framework can be adapted to specific development contexts and thereby made more universal, by suggesting relevant well-being dimensions and indicators that could be used to measure well-being in developing countries. Finally, it discusses the possible implications of the adapted framework for OECD work in developing countries, in particular its possible use in the Multi-Dimensional Country Reviews conducted by the OECD Development Centre for a range of non OECD countries